PENYULUHAN TENTANG DAMPAK DARI BUANG SAMPAH SEMBARANGAN DI WILAYAH MASYARAKAT PESISIR KOTA BENGKULU - Emi Kosvianti; Nopia Wati; Agus Ramon; Hersanti, Fitri (Gayaku Publisher, 2023)
Coastal communities are mostly fishing communities that have different characteristics from other communities. This difference is due to its close relationship with the economic characteristics of coastal areas, cultural background and the availability of supporting facilities and infrastructure. In general, coastal communities have cultural values ​​that are oriented towards being in harmony with nature, so that technology utilizing natural resources is an adaptive technology to the conditions of coastal areas. Garbage is an opportunity for environmental pollution accompanied by a decrease in aesthetic quality. The population can also influence the increase in the amount of waste. Apart from that, people's behavior of throwing rubbish on the coast is also a habit that can have a negative impact. 1 Based on data obtained from initial observations by the Community Service Student team in the Coastal area at Jalan Enggano 1 RT 04, Pasar Bengkulu Village, Sungai Serut District, waste management in this area is said to be very lacking, some residents even say there is none. And from the team's observations, it was found that in the area of ​​Jl Enggano 1 RT 04, Pasar Bengkulu Village, Sungai Serut District, rubbish was still often found scattered in the yards of several residents' houses and on the side of the roads in the area. And very few residents' homes have private rubbish boxes and rubbish incinerator. This is the background for our team to carry out community service activities, namely